Comparative Analysis of Routine Immunization Policy During COVID-19 Pandemic in Indonesia, India, and Pakistan - Delfyan, Dian Trisna; Ilyas, Yaslis (UI Scholars Hub, 2021)
Immunization is one of the most cost-effective public health interventions, averting an estimated 2 to 3 million deaths every year. Before the coronavirus pandemic, more than nearly 14 million children didn't receive any vaccines, and 19 million children below the age did not receive the recommended vaccines in 2019. COVID 19 is leaving many of the world's most marginalized children without access to immunization services. Some are from Indonesia, India, and Pakistan, including ten countries with the highest number of unimmunized and partially immunized children. The study aims to find out the differences in the policy of routine immunization programs during the COVID-19 Pandemic in Indonesia, India, and Pakistan in terms of policy actors, policy context, policy process, and policy content. The method used is a literature review from sources such as books, journals, and relevant government regulations and policies related to routine immunization programs during the COVID-19 Pandemic. Literature study shows that the three countries have some similarities in the policy actors, policy context, and policy process. The only difference is the policy content. The policy in the form of technical guidance by the Indonesian government is more detailed, comprehensive, and structured than the other two countries.